Governance Teknologi di Masyarakat : Sebuah Pendekatan Jejaring-Aktor - S. Yuliar S. Yuliar; M.A. Anggorowati M.A. Anggorowati (Fakultas Seni Rupa dan Desain ITB, 2006)
Technology governance in community relates to the coordination, technology steering and operation which are aimed at the achievement of the predicted or ntended social impact. The mutual shaping between technology and community implies that technology governance has to take into account of technology diffusion and innovation whose process is co-evolutionary in nature. In this paper, a methodological framework which is designed to understand technology governance is based on actor-network theory. A case study about the implementation of technology scanner to process a census of population data is presented to ilustrate the application of the above-mentioned methodological framework. The problems found during the research are also presented at the last part of this paper. Kata Kunci: governance teknologi, mutual shaping teknologi dan masyarakat, proses ko-evolusioner, teori jejaring-aktor.